Santa Thereza: um estudo sobre as charqueadas da fronteira Brasil - Uruguai - Soares, Fernanda Codevilla (2006)
This work has for objective to analyze the life riograndese in ends of century XIX and principles of century XX, emphasizing the frontier character of the dried meat s industry and its entailing to the platino space, especially Uruguai. The Charqueada Santa Thereza, established in the city of Bagé in 1897, it is the object of study of this work. Such establishment has as proprietor Ribeiro de Magalhães. The dried meat s industry ones of this period are endowed with a series of characteristics that differentiate them of gauchos slaveries dried meat s industry the slaveries, between these, we can cite: wage-earning man power, work in series, use of machine in the process of manufacture of dried meat, diversified production (other products beyond dried meat) etc. These characteristics become such similar establishments the platinos dried meat s industry, that since early already have these elements and competed as the market gaucho in the commerce of dried meat. The contact with the platino space was given through commercial and cultural, legal and illicit the exchanges, between the brazilian and uruguayan proprietors, which could have been analyzed during the development of the research. The used sources had been: old ruin, letters and periodicals photos the urban complex built in around of the industry. The work intends a new to look at on the subject, since it privileges the entailings of these establishments with the Prata and uses sources diversified for the historical research.